(untitled) - Nguyen, Thi Huyen (Netherlands, 2016)
The world population growth and rising incomes are expected to increase the consumption of animal-derived foods such as meat, eggs and milk. However, livestock production should not only be directed towards increasing productivity but should also incorporate environmental, food safety and animal welfare aspects. Therefore, farm businesses have to respond to the high environment impact of their activities, by using low-input systems including the use of forage legumes. Recent studies have demonstrated that forage legumes with moderate levels of condensed tannins (CT) are beneficial for animal nutrition and animal health. Sainfoin (Onobrychis viciifolia Scop.) is a tanniniferous forage legume containing CT that has potential nutritional and health benefits, i.e. preventing bloating, reducing nematode larval establishment, improving nitrogen (N) utilization and reducing greenhouse gas and N emissions (Chapter 1). However, the use of sainfoin as a fodder crop in dairy cow rations in northwestern Europe is still rather unknown. This thesis investigated the potential of sainfoin in the dairy cow diets and the effect of CT structural properties on rumen fermentation and biohydrogenation (BH).
Keywords: Gia súc,Cattle; Thức ăn và cho ăn,Feeding and feeds